Profil ekspresi HER2 dan Ki67 pada berbagai kelompok usia penderita kanker payudara di RSUP H. Adam Malik Medan - Santer dr; Kamal Basri Siregar; Suyatno dr (Majalah Kedokteran Nusantara The Journal Of Medical School, 2013)
Introductions : Breast cancer is commonly found in old age. Many genes had been reported to be involved in the carcinogenesis of breast carcinoma, such as p53, Ki67, cathepsin D, and HER2. Some studies reported that HER2 overexpression associated with age. Ki67 levels are associated with poor disease free survival.The aim of this study was to determine the level of overexpression of HER2 and Ki67 in the various age groups of breast cancer patients in H. Adam Malik Hospital Medan.Methods: This study was a descriptive cross sectional study, by examining Ki67 by immunohistochemistry in 40 paraffin blocks of breast cancer patients who had diagnosed in HER2 by immunohistochemistry examination. Specific cut off point of Ki67 was 14%.Results: 40 female samples had been studied. The majority of respondents are 35-50 years age group (45%). HER2 (+) were 12 samples and HER2 (-) were 28 samples. HER2 (+) was found in the 51-65 year age group of 6 sample (50%). Over expression of Ki67 were found in 28 samples and low expression in 12 samples. Over expression of Ki67 in the age group >65 years were 3 samples (100%).Conclusion: Over expression of HER2 and Ki67 found more in older age groups, based on the number of samples in each age group.Keywords: age; HER2 expression; Ki67 expression